Starfall as a Catalyst for Kuwaiti EFL Young Learners’ Reading Comprehension: A Teacher’s Reflections - Bataineh, Ruba; Al-Ghareeb, May Bader (Journal of Ethnic and Cultural Studies, 2025)
This study examines the effect of a Starfall-based instructional program on second-grade pupils’ reading comprehension in a Kuwaiti public school in the first semester of the academic year 2023/2024. The participants were divided into a control group taught conventionally per the guidelines of the Ministry of Education and an experimental group taught using Starfall-based instruction. Using an observation card and a teacher’s journal, the research highlights improvements in the experimental group’s engagement, motivation and comprehension. Emerging themes include increased student participation, improved classroom dynamics, and technology integration as a catalyst for literacy. The findings emphasize the potential of interactive applications, of which Starfall is one, to support EFL instruction. The researchers put forth practical recommendations for incorporating technology in the early-grade EFL classroom, as the findings provide valuable insights for educators aiming to innovate EFL teaching practices.